0984 Daily Positive Affect Predicts EEG-Determined REM Duration. (27th April 2018) - Hale, B S; Messman, B; Brown, A; Banzuelo, H; Nguyen, T; Slavish, D; Taylor, D J; Dietch, J R
Abstract: Introduction: Research has established the detrimental impact of short REM duration on negative affect. However, the relationship between REM duration and positive affect is understudied, particularly using objective measures of sleep in naturalistic settings. The present study sought to determine if nightly REM duration was associated with self-reported positive and negative affect (PA and NA, respectively), captured daily in a community sample for one week. Methods: Participants ( N = 87; 64% female; M age = 33.2 [ SD = 10.6]) completed a baseline psychosocial questionnaire followed by one week of morning diaries and at-home single-channel EEG monitoring. The previous day's PA and NA were reported each morning using an abbreviated version of the Positive and Negative Affect Schedule. REM duration was determined via EEG. Multilevel models (controlling for age, gender, and BMI) were conducted. Results: There was significant (p < .0001) variation in PA, NA, and REM duration from person-to-person and from day-to-day. When PA and NA were examined separately, days with greater PA than average were associated with nights with longer REM duration (β = 0.17, SE = 0.06, p = 0.003), and there was a trend for days with greater NA than average being associated with shorter REM duration (β = 0.20, SE = 0.12, p = 0.08). When PA and NA were examined simultaneously, PA remained associated with REM duration ( p = 0.006), while NA no longer showed a trend ( p = .16). REM duration did not predict the subsequent day's PA or NA. Conclusion: This was the first study to examine daily relationships between affect and an objective measure of REM duration in a naturalistic setting across one week. Results from this study suggest that PA is more strongly associated with REM duration than NA, and affect is a more robust predictor of sleep than vice versa. Future studies should examine if these results replicate using more sophisticated measures of sleep (e.g., full PSG). Support (If Any): This research was supported by an In-Kind grant from General Sleep Corporation and the Foundation for Rehabilitation Psychology Dissertation Award.